Germ cell tumour growth patterns originating from clear cell carcinomas of the ovary and endometrium: a comparative immunohistochemical study favouring their origin from somatic stem cells. Issue 4 (21st December 2017) - Nogales, Francisco F; Prat, Jaime; Schuldt, Maolly; Cruz‐Viruel, Nelly; Kaur, Baljeet; D'Angelo, Emanuela; Matias‐Guiu, Xavier; Vidal, August; McCluggage, W Glenn; Oosterhuis, J Wolter
Abstract : Aims: To report a series of 11 ovarian and one endometrial neoplasm in elderly patients with mixed clear cell tumour and germ cell tumour (GCT) components, to compare their immunohistochemical profiles and demonstrate a putative stem cell population. Methods and results: The clear cell tumours included 11 clear cell carcinomas (CCC) and one borderline clear cell tumour, while the GCT always included glandular yolk sac tumour (YST). In four cases, there were also foci of teratoma with immature neuroepithelial and endodermal tissues and undifferentiated areas showing true embryoids. To distinguish between the clear cell and YST components, the following antibodies were used: HNF1‐β, napsin‐A, cytokeratin 7 (CK7), PAX8, EMA, AFP, SALL4, villin, glypican‐3 (GPC‐3), GATA3, HepPar‐1, OCT4, CDX2, CD30 and SOX2. HNF1‐β, CK7, EMA and GPC‐3 were often expressed in both components. Other markers had higher specificity for each cellular lineage; napsin‐A and PAX8 were expressed only in CCC, while SALL4, villin, AFP and HepPar‐1 were positive in the glandular YST component but negative in the clear cell component. OCT4 expression occurred in six of 10 cases and consistently in teratoma (four of four). Conclusions: There is considerable immunophenotypical overlap between the two components in these mixed neoplasms, and a panel of markers should be used to facilitate the distinction. We propose that OCT4‐expressing somatic cancer cells differentiate into GCT and represent spontaneously induced pluripotent stem cells, possibly conditioned by age‐related epigenetic factors. These neoplasms have features of prepubertal type GCT showing lack of 12p gain, preponderance of YST and coexistence with immature neuroectoderm. However, there may also be undifferentiated stem cell areas with embryoid bodies, of the type seen in postpubertal testicular GCT, but lacking a complete embryonal carcinoma immunophenotype.